ByzRev 07.2025.047: Przemysław Marciniak – Tristan Schmidt (eds), The Routledge Handbook of Human-Animal Relations in the Byzantine World: (Routledge History Handbooks). Abingdon: Routledge 2025. - Lauxtermann, Marc (The Byzantine Review, 2025)
Przemysław Marciniak – Tristan Schmidt (eds), The Routledge Handbook of Human-Animal Relations in the Byzantine World (Routledge History Handbooks). Abingdon: Routledge 2025. 366 pp. – ISBN 978-0-367-51964-3